Comparison of the effects of IVth ventricular administration of some tryptamine analogues with those of 8-OH-DPAT on autonomic outflow in the anaesthetized cat. - Shepheard, S. L. (1994)
1 The present study compares the effects on representative autonomic outflows of IVth ventricular application of tryptamine analogues which act at 5-HT1 receptors with 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT). 2 Cumulative doses of 8-OH-DPAT, N,N-di-n-propyl-5-carboxamidotryptamine (DP-5-CT) and 5-carboxamidotryptamine (5-CT, 2.5-40 nmol kg-1), sumatriptan (10-160 nmol kg-1), indorenate (100-800 nmol kg-1), 5-hydroxytryptamine (5-HT, 20-640 nmol kg-1) both alone and in the presence of cinanserin (0.1 mg kg-1) were given into the IVth ventricle of cats which were anaesthetized with a mixture of alpha-chloralose and pentobarbitone sodium, neuromuscularly blocked and artificially ventilated. Recordings were made of arterial blood pressure, heart rate, renal, cardiac, splanchnic and phrenic nerve activities, femoral arterial flow, tracheal and intragastric pressures. 3 Central application of each of the agonists evoked significant falls in arterial blood pressure. In addition 8-OH-DPAT, DP-5-CT, 5-CT and 5-HT all evoked a differential inhibition of sympathetic nerve activities, with renal nerve activity being the most sensitive and cardiac nerve activity the least sensitive. In the dose-ranges used, administration of sumatriptan evoked reductions only in renal and splanchnic nerve activities whilst indorenate reduced activity in all three sympathetic nerves to a similar extent. 4 The effect of the agonists on heart rate was more inconsistent than the effects on sympathetic outflow.(ABSTRACT TRUNCATED AT 250 WORDS)